Dictyna arundinacea - Marusik, Yuri M. (Zenodo, 2022)
Dictyna arundinacea (Linnaeus, 1758) (Figures 1a – e, h, 2, 4) Aranea arundinacea Linnaeus, 1758: 620 (sex not specified). Dictyna ignobilis Kulczyński, 1895: 31, pl. 1, figs 19 (♀). syn. Nov. Dictyna arundinacea : Crews et al. 2020: 912, figs 20E, I, K–L, S11A–H, S12D–E (♂ ♀). For the complete list of 81 taxonomic references see WSC (2022). Material examined Holotype ♀ and paratype 1 ♂ juv. from IZ PAN with museum label ‘ Armenia: Elenovka, ad lacum Goktsha, 9.VI. leg. G. Horwath’ (Figure 1f, modern name Sevan Town on Sevan Lake) and original label ‘ Armenia ♀, ♂ juv. Bessarabia’ (Figure 1g); 1♂ 20 juv. (ZMMU), ARMENIA, Gegharkunik Province, Sevan Lake, env. of Tsovagyugh Town, 40.615°N 44.968°E, 1920 m, lake shore, in dry collective fruits (= inflorescence) of Astragalus sp., 8 May 2021 (Y.M. Marusik). Note Holotype ♀ (Armenia) and paratype subadult male (Bessarabia) are from very widely separated localities (ca. 1500 km). Brief description Holotype female. General appearance as in Figure 1a–b, h. Total length 3.0. Carapace 1.25 long, cephalic part 0.83 wide, thoracic part 0.95 wide. Leg length as shown in Table 1. Epigyne as in Figure 1c–e. Topotype male. General appearance as in Figure 2d, g–h. Total length 2.63. Carapace 1.25 long, cephalic part 0.63 wide, thoracic part 1.0 wide. Leg length as shown in Table 2. Palp as in Figure 2a–c. Comments The endogyne of the holotype female of D. ignobilis is undistinguishable from that of D. arundinacea . The adult male specimen collected about 10 kilometres from the type locality has no distinct differences in the palp from that of D. arundinacea , and therefore the two names are synonymised here. The slight apparent differences between the male palps of specimens from Armenia (Figure 2a–c) and Yakutia (Figure 2d–e) are caused by different positions of the palps during photography. Distribution Dictyna arundinacea has a circum-Holarctic range and is known across the whole Palaearctic from Iceland to Kamchatka (Marusik et al. 2000), and throughout the Nearctic from ...